2000
DOI: 10.1146/annurev.phyto.38.1.491
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Wheat Leaf and Stem Rust in the Central Great Plains of the USA

Abstract: Wheat (Triticum aestivum L) is grown throughout the grasslands from southern Mexico into the prairie provinces of Canada, a distance of nearly 4200 km. The total area seeded to wheat varies considerably each year; however, from 28 to 32 million ha are planted in the Great Plains of the United States alone. Generally in the central Great Plains, an area from central Texas through central Nebraska, 15 million ha are seeded to winter wheat each year. A wide range of environmental conditions exist throughout this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 25 publications
1
80
0
4
Order By: Relevance
“…tritici (pgt) contributes great losses to wheat produce. 2,5,21,22 Here we report our findings for disease intensity (leaf, stem and yellow rusts) on wheat genotypes at various locations (Tables 3-6). Genotypes showed distinct response to different rusts (leaf, yellow and stem rust).…”
Section: Resultsmentioning
confidence: 89%
“…tritici (pgt) contributes great losses to wheat produce. 2,5,21,22 Here we report our findings for disease intensity (leaf, stem and yellow rusts) on wheat genotypes at various locations (Tables 3-6). Genotypes showed distinct response to different rusts (leaf, yellow and stem rust).…”
Section: Resultsmentioning
confidence: 89%
“…Wennström & Eriksson (1997) have shown that the heteroecious rust, Gymnosporangium cornutum, could not survive during winter in its secondary host S. aucuparia and that infection on this species relied on spore dispersal from its primary host Juniperus communis (in this case, spore dispersal is effective up to 50 m away from the primary host). The role of alternative hosts of cereal rusts (leaf rust caused by Puccinia triticina, stripe rust caused by Puccinia striiformis and stem rust caused by Puccinia graminis) on summer or winter survival of the pathogens has been considerably studied in North America but remains unclear (Eversmeyer & Kramer 2000;Line 2002). A well-studied example is the case of the heteroecious stem rust in the USA.…”
Section: Impact Of Landscape Composition On Global Pathogen Propagulementioning
confidence: 99%
“…As is characteristic of many residue-borne and soilborne pathogens, the number of generations of P. tritici-repentis generally is low during a growing season and its dispersal gradient is steep (41). In contrast, Puccinia triticina, the causal agent of leaf rust, is typical of many windborne pathogens in that it is highly specialized, polycyclic, and follows a shallow dispersal gradient (10).…”
mentioning
confidence: 99%